A cross‐sectional survey of occupational history as a wildland firefighter and health. Issue 4 (21st January 2016) - Semmens, Erin O.; Domitrovich, Joseph; Conway, Kathrene; Noonan, Curtis W.
Abstract : Background: Little is known regarding the impact of long‐term wildland firefighting on health. Our objective was to investigate associations between duration of wildland firefighting experience and the prevalence of self‐reported health outcomes. Methods: We ascertained employment, health, and demographic information on 499 current wildland firefighters (WLFFs) via questionnaire. Results: Relative to those with less than 10 years of experience as a WLFF, those with 10–19 years of experience had significantly greater odds of having ever been diagnosed with hypertension, as did those with 20 or more years of experience. Significant associations were observed for report of physician‐diagnosed heart arrhythmia and previous knee surgery. Conclusions: We observed significant links between a greater number of years as a WLFF and self‐report of two subclinical cardiovascular risk factors as well as markers of musculoskeletal health. Additional studies are needed to determine if findings can be generalized to all WLFFs. Am. J. Ind. Med. 59:330–335, 2016. © 2016 Wiley Periodicals, Inc.